2002
DOI: 10.1097/00006534-200204150-00023
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Fat Grafts in Recipient Areas with Enhanced Vascularity

Abstract: Fat grafts are used for soft-tissue augmentation of various anatomic regions, most frequently for the improvement of facial contours. Resorption of the graft is the main problem, and several different procedures have been described to minimize this phenomenon. Using 25 New Zealand rabbits, the behavior of fat grafts in a highly vascularized recipient site was studied. The recipient sites prepared on the backs of the rabbits were divided into four regions. A capsule formation with silicone sheet application was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…Despite numerous clinical studies presented in the literature [for reviews see 3,15,16,23], a consensus on the sustainability of transplanted fat grafts and the proper methods to obtain and store these grafts has yet to be reached. Those animal studies that have been presented are also conflicting in their results, with good retention being reported in rodents [24] yet significant resorption being observed in rabbit models [25,26]. Consistent with these rabbit studies, injection of fresh grafts performed in this study was accompanied by loss of total weight over time together with a definitive loss in adipose tissue structure as the number of adipocytes decreased and the amount of fibrous tissue within these fresh grafts increased.…”
Section: Discussionsupporting
confidence: 71%
“…Despite numerous clinical studies presented in the literature [for reviews see 3,15,16,23], a consensus on the sustainability of transplanted fat grafts and the proper methods to obtain and store these grafts has yet to be reached. Those animal studies that have been presented are also conflicting in their results, with good retention being reported in rodents [24] yet significant resorption being observed in rabbit models [25,26]. Consistent with these rabbit studies, injection of fresh grafts performed in this study was accompanied by loss of total weight over time together with a definitive loss in adipose tissue structure as the number of adipocytes decreased and the amount of fibrous tissue within these fresh grafts increased.…”
Section: Discussionsupporting
confidence: 71%
“…Previous work has shown that recipient-site characteristics such as vascularity are important for the regeneration of new bone tissue and support of grafted tissue. [18][19][20] For mandibular reconstruction, the defect site and surgical approach along with recipient-site complications such as infection, intraoral exposure, and prolonged antibiotic use have been significantly linked to graft failure. 21,22 An ideal temporary space maintainer will therefore not only maintain the osseous void and prevent soft tissue collapse or contracture into the space, but also will allow or promote soft tissue coverage and healing without serving as a nidus for local infections.…”
Section: Introductionmentioning
confidence: 99%
“…At week 2 and week 4 after auto-transplantation, the survival rates in experimental group are higher than that in control group without statistically difference (p [ 0.05). The survival rates in experimental group were statistically greater than the control group in week 12 after auto-transplantation (p \ 0.05) a Compared with the Control Group (Group I), p \ 0.05 In view of studies concerning adipose tissue transplantation in recent years, it is quite clearly indicated that revascularization in an early phase plays a rather pivotal role in the survival state of the adipose graft [16][17][18]. S. miltiorrhiza, ranked as a ''Supergrade'' medicine in Shen Nung Pen Ts'ao Ching (one of most famous traditional medicine directory in China), has been used widely in Asia for a long time to treat angiogenesis-and hemostasis-related diseases such as atherosclerosis, thromboembolism, and angina.…”
Section: Discussionmentioning
confidence: 95%
“…Lots of efforts have been made to improve this situation including harvest techniques, adipose tissue manipulations, injection skills, and other surgical approaches [7][8][9][10][11][12][13][14][15]. For the past decades, the perspective that neovascularization in the early phase is pivotal in improving adipocyte survival rate has been widely accepted [16][17][18]. Thereby, all kinds of growth factors, e.g., VEGF, bFGF, IGF-1, HGF, EGF, etc., have been explored hoping to reduce the absorbance and most of them achieved satisfying results [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%